The Template for Intervention Description and Replication as a Measure of Intervention Reporting Quality: Rasch Analysis - Dijkers, Marcel P. (Arch Rehabil Res Clin Transl, 2020)
OBJECTIVE: To determine whether the 12 items of the Template for Intervention Description and Replication (TIDieR) can be combined into a single summary score reflecting intervention reporting completeness and quality. DESIGN: Systematic review and reanalysis of published data. After a systematic search of the published literature, 16 review articles were retrieved with 489 sets of 12 TIDieR ratings of experimental intervention, comparator, or the 2 combined as reported in primary studies. These 489 sets were recoded into a common format and analyzed using Rasch analysis for binary items. SETTING: Not applicable. PARTICIPANTS: Not applicable. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURES: Psychometric qualities of a Rasch Analysis-based TIDieR summary score. RESULTS: The data fit the Rasch model. Infit and outfit values were generally acceptable (range, 0.70-1.45). TIDieR was reasonably unidimensional in its structure. However, the person (here: study) separation ratio was 1.25 with a corresponding reliability of 0.61. In addition, the confidence interval around each estimate of reporting completeness was wide (model standard error of 0.78) CONCLUSION: Several Rasch indicators suggested that TIDieR is not a strong instrument for assessing the quality of a researcher’s reporting on an intervention. It is recommended that it be used with caution. Improvements in TIDieR itself may make it more helpful as a reporting tool.